Point-of-care testing in neurosurgery - Beynon, Christopher; Wessels, Lars; Unterberg, Andreas (Seminars in thrombosis and hemostasis, 2017)
Coagulation disorders can have a major impact on the outcome of neurosurgical patients. The central nervous system is located within the closed space of the skull, and therefore, intracranial hemorrhage can lead to intracranial hypertension. Acute brain injury has been associated with alterations of various hemostatic parameters. Point-of-care (POC) techniques such as rotational thromboelastometry are able to identify markers of coagulopathy which are not reflected by standard assessment of hemostasis (e.g., hyperfibrinolysis). In patients with acute brain injury, POC test results have been associated with important outcome parameters such as mortality and need for neurosurgical intervention. POC devices have also been used to rapidly identify and quantify the effects of antithrombotic medication. In cases of life-threatening intracranial hemorrhage, this information can be valuable when deciding over administration of prohemostatic substances or immediate neurosurgical intervention. In elective neurosurgical procedures, POC devices can provide important information when unexpected bleeding occurs or in cases of prolonged operative time with subsequent blood loss. Initial experiences with POC devices in neurosurgical care have shown promising results but further studies are needed to characterize their full potential and limitations